Application of biochar-based catalysts in biomass upgrading: a review - Cao, Xuefei; Sun, Shaoni; Sun, Runcang (RSC advances, 2017)
Biochar is a low-cost carbon-rich material derived from the thermochemical degradation of biomass. Due to its unique chemical structure, biochar with a large surface area and tailored surface functional groups can be easily prepared by activation and/or functionalization, and shows great potential to be used as a versatile catalyst and/or catalyst support in many chemical processes. However, the application of biochars as versatile catalysts and/or catalyst supports for biomass upgrading has not been systematically overviewed so far. In this work, the formation of pyrochar and hydrochar is proposed, and the activation and/or functionalization of biochar are also included. Subsequently, the application of biochar-based catalysts in biomass upgrading, including biochar-based solid acids for biomass hydrolysis and dehydration, biochar-based catalysts for biodiesel production, and biochars as catalyst supports for biomass pyrolysis, gasification, and bio-oil upgrading, are discussed in detail. The application of biochars as versatile catalysts and/or catalyst supports for biomass upgrading is systematically overviewed.